An anticorrosive electronic-grade coating agent and a preparation method thereof
By preparing a fluorosilicone resin coating agent, the problems of insufficient adhesion and insulation of existing coating agents are solved, achieving effective anti-corrosion protection in complex environments, which is suitable for electronic components.
Patent Information
- Application Number
- CN202610544692.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-04-23
- Publication Date
- 2026-06-26
AI Technical Summary
Existing anti-corrosion coatings are inadequate in terms of adhesion and insulation, and cannot effectively protect electronic components from corrosion in complex environments, especially performing poorly in harsh environments.
Fluorosilicone resin is prepared by using components such as acrylate, fluorinated acrylate, fluorosilicone resin, coupling agent and initiator through specific reaction steps to form a dense coating, which improves adhesion and insulation. Fluorine element is evenly distributed to provide hydrophobic and oleophobic effects.
The prepared coating agent has excellent adhesion and insulation properties, effectively protecting electronic components from corrosion. It is suitable for various environments, especially performing well in harsh environments.
Smart Images

Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of coating technology, and specifically to an anti-corrosion electronic-grade coating agent and its preparation method. Background Technology
[0002] In today's rapidly developing electronics and information industry, electronic components are constantly evolving towards miniaturization, high density, and high integration. Their working environments are also becoming increasingly complex and diverse, making corrosion protection a crucial factor in ensuring the stability and lifespan of electronic equipment. During production, storage, transportation, and practical application, electronic components are susceptible to corrosion from humidity, temperature changes, and chemical media (such as salts, sulfides, and contaminants), leading to problems such as metal pin oxidation, short circuits, and signal transmission attenuation. In severe cases, this can even cause equipment failure and result in significant economic losses. Industry statistics show that corrosion-related failures account for over 30% of electronic equipment failures, especially in harsh environments such as automotive electronics, aerospace, and marine engineering, where this proportion is even higher. Therefore, the demand for high-performance corrosion-resistant electronic-grade coatings is extremely urgent.
[0003] Patent CN113683934B discloses a highly transparent and washable acrylic anti-corrosion coating, comprising the following raw materials in parts by weight: 100-400 parts organic solvent; 3-120 parts acrylate monomer; 1-50 parts fluorinated acrylate monomer; 0.1-20 parts fluorosilicone macromonomer; 0.05-20 parts thickener; 0.01-5 parts coupling agent; and 0.01-2 parts initiator. This invention's highly transparent and washable acrylic anti-corrosion coating not only possesses excellent hydrophobic properties and good anti-corrosion effect, but also boasts advantages such as high adhesion, high transparency, and washability. Furthermore, it exhibits mild reaction conditions and excellent mechanical properties, meeting the needs of various practical applications such as PCB anti-corrosion. However, the adhesion of the coating to the substrate has not been studied.
[0004] Patent CN112409889A discloses a UV nano-anti-corrosion coating, the resulting circuit board, its preparation method, and its application. The circuit board with the anti-corrosion coating of this invention includes a circuit board, a primer coating, and a UV nano-anti-corrosion coating layer. The UV nano-anti-corrosion coating layer is prepared from the following raw materials in parts by weight: 20-40 parts UV resin, 20-40 parts acrylate monomer, 3-8 parts initiator, 0.5-2 parts rust inhibitor, 1-5 parts superhydrophobic nanoparticles, and 1-5 parts additives. The invention also provides a method for preparing the above-mentioned UV nano-anti-corrosion coating layer. This invention's UV nano-anti-corrosion coating layer has a scientifically formulated composition, a reasonable anti-corrosion coating design for the circuit board, high adhesion, good hydrophobic properties, effectively preventing the penetration of droplets and corrosive media into the circuit board, good long-term waterproof performance, strong corrosion resistance, a simple preparation method, convenient operation, low equipment requirements, and is easy to industrialize. It is particularly suitable for white goods and electronic products in coastal or near-shore areas. However, for the stability of circuit signal transmission, the coating needs excellent electrical insulation properties; however, the electrical properties of the coating have not been studied.
[0005] Therefore, there is an urgent need in the market to develop an anti-corrosion coating agent with excellent adhesion and insulation properties. Summary of the Invention
[0006] In view of the problems existing in the prior art, the purpose of this invention is to obtain an anti-corrosion coating agent with excellent adhesion and insulation.
[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows: The first aspect of the present invention provides an anti-corrosion electronic-grade coating agent, comprising, by weight, the following raw materials: 5-8 parts of acrylate, 10-20 parts of fluorinated acrylate, 9-11 parts of fluorosilicone resin, 0.6-2 parts of coupling agent, 0.06-1 part of initiator, and 80-130 parts of hydrofluoroether.
[0008] In some embodiments, the acrylate is acrylic acid, methacrylic acid and its derivatives, hexanediol diacrylate, ethylene glycol dimethacrylate, ethoxylated trimethylolpropane triacrylate, trimethylolpropane triacrylate, pentaerythritol triacrylate and pentaerythritol tetraacrylate.
[0009] In some embodiments, the derivatives include esters, nitriles, amides, and silanes.
[0010] Preferably, the acrylate is a mixture of methacrylate, hexanediol diacrylate and pentaerythritol tetraacrylate, wherein the mass ratio of the three is 1:(0.2-0.5):(0.1-0.3).
[0011] In some embodiments, the fluorinated acrylate is any one or more of tridecylfluorooctyl methacrylate, dodecafluoroheptyl methacrylate, and hexafluorobutyl methacrylate.
[0012] In some embodiments, the method for preparing the fluorosilicone resin includes the following steps: 1) Maleic anhydride, 5,5,5-trifluoropentanol, and a polymerization inhibitor are added to toluene and reacted at 45-55℃ for 24-36 h. After drying, an intermediate is obtained. Under nitrogen protection, the intermediate, 3-isocyanate-propyltrimethoxysilane, and triethylamine are added to acetone and reacted at 70-80℃ for 1-2 h. After drying, the product is obtained. 2) Under inert gas protection, γ-(2,3-epoxypropoxy)propyltrimethoxysilane and 3,3,3-trifluoropropylamine were added to anhydrous ethanol, heated to 60-70℃ and reacted for 40-50 h, cooled to room temperature, and then the product obtained in step 1) and ammonia water were added, heated to 45-55℃ and reacted for 2-3 h, and dried to obtain fluorosilicone resin.
[0013] In some embodiments, the polymerization inhibitor is hydroquinone or hydroquinone.
[0014] Preferably, the polymerization inhibitor is p-benzodiquinone.
[0015] In some embodiments, the molar ratio of the polymerization inhibitor to maleic anhydride is (0.05-0.15):1.
[0016] Preferably, the molar ratio of the polymerization inhibitor to maleic anhydride is (0.08-0.12):1.
[0017] In some embodiments, the concentration of the ammonia solution is 5-15 wt%.
[0018] Preferably, the concentration of the ammonia water is 10 wt%.
[0019] In some embodiments, the ratio of ammonia to γ-(2,3-epoxypropoxy)propyltrimethoxysilane is (1ml-5ml):1g.
[0020] Preferably, the ratio of ammonia water to γ-(2,3-epoxypropoxy)propyltrimethoxysilane is 3 ml: 1 g.
[0021] Traditional fluorosilicone resins simply mix fluorocarbon chains with polysiloxanes. The resulting protective film is not dense enough and is easily corroded by moisture, leading to a decrease in protective performance. This invention addresses this by reacting maleic anhydride and 5,5,5-trifluoropentanol in a controlled ratio to retain a carboxyl group before reacting with 3-isocyanate-propyltrimethoxysilane to generate a substance containing silane, amide bonds, fluoroalkyl groups, and unsaturated double bonds. Simultaneously, epoxy silane is reacted with fluoroamines and then condensed with the product obtained in step 1). The resulting fluorosilicone resin can copolymerize with other monomers under the action of an initiator, resulting in a coating with good density. Furthermore, the residual hydroxyl groups after epoxy ring opening enhance adhesion to the substrate, making it suitable for various environments and improving corrosion resistance. Additionally, by placing the fluorinated segments close to the amide and ether bonds, this invention may facilitate a more uniform distribution of fluorine, allowing it to stably and efficiently exert its low surface energy properties, providing long-lasting and excellent hydrophobic and oleophobic effects. This multi-faceted approach enhances corrosion resistance.
[0022] In some embodiments, the molar ratio of maleic anhydride to 5,5,5-trifluoropentanol in step 1) is 1:(1-1.2).
[0023] In some embodiments, the mass ratio of the intermediate described in step 1) to 3-isocyanate-propyltrimethoxysilane is 1:(0.8-1.3).
[0024] In some embodiments, the mass ratio of γ-(2,3-epoxypropoxy)propyltrimethoxysilane to 3,3,3-trifluoropropylamine and the product in step 2) is 1:(0.5-0.7):(1.5-2).
[0025] In some embodiments, the coupling agent is any one or more of γ-(methacryloyloxy)propyltrimethoxysilane, 3-aminopropyltriethoxysilane, and N-β-aminoethyl-γ-aminopropyltrimethoxysilane.
[0026] In some embodiments, the hydrofluoroether is any one or more of methyl nonafluorobutyl ether, methyl nonafluoroisobutyl ether, methyl perfluoropropyl ether, ethyl perfluorobutyl ether, 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, trifluoroethyl hexafluoropropyl ether, perfluorononylpentafluoroethyl ether, and 3-methoxyperfluoroethane.
[0027] In some embodiments, the initiator is any one or more of azobisisobutyronitrile, benzoyl peroxide, potassium persulfate, and ammonium persulfate.
[0028] A second aspect of this invention provides a method for preparing an anti-corrosion electronic-grade coating agent, comprising the following steps: Under nitrogen protection, acrylate, fluorinated acrylate, fluorosilicone resin, coupling agent, initiator and hydrofluoroether are stirred at 60-70℃ for 4-12 hours and then rotary evaporated to obtain coating agent.
[0029] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention provides a coating agent prepared by acrylate, fluorinated acrylate, fluorosilicone resin, coupling agent, initiator and hydrofluoroether. It has good adhesion to the substrate, high insulation and good corrosion resistance, wide range of applications, and safe operation without flash point.
[0030] (2) On the one hand, the present invention utilizes maleic anhydride and 5,5,5-trifluoropentanol to react to obtain an intermediate, which is then reacted with 3-isocyanate-propyltrimethoxysilane to obtain a product. On the other hand, γ-(2,3-epoxypropoxy)propyltrimethoxysilane reacts with 3,3,3-trifluoropropylamine and then condenses with the product obtained in step 1) to obtain a fluorosilicone resin. This is beneficial for forming a coating with good density with other components, solving the problem that the protective film formed after coating by conventional coating agents is not dense enough and is easily corroded by water vapor, resulting in a decrease in protective performance. In addition, the fluorosilicone resin prepared by the present invention may have a more uniform distribution of fluorine, which can provide a long-lasting and excellent hydrophobic and oleophobic effect, thus improving the corrosion resistance in multiple ways. Detailed Implementation
[0031] The present invention will be described below with reference to specific embodiments. It should be noted that the following embodiments are examples of the present invention and are used only to illustrate the invention, not to limit it. Other combinations and various modifications within the scope of the present invention can be made without departing from its spirit or scope.
[0032] In the following examples and comparative examples, except for the flame retardant, all other compounds and related reagents used were commercially available. Among them, the fluorosilicone resin LS-8722 was purchased from Hubei Shuaiyan Ligao Biomedical Co., Ltd., and the solvent Kefrier400 was purchased from Kaiyi New Materials Technology (Shanghai) Co., Ltd.
[0033] Unless otherwise specified, the post-processing steps such as "rotary evaporation", "drying", "extraction", and "reduced pressure distillation" used below are routine operations for those skilled in the art, and can be selected according to actual operation.
[0034] Preparation Example 1 The preparation method of fluorosilicone resin-1 includes the following steps: 1) Add 1 mol of maleic anhydride, 1.1 mol of 5,5,5-trifluoropentanol, and 0.1 mol of p-benzoquinone to 200 ml of toluene, react at 50 °C for 30 h, and dry to obtain an intermediate; under nitrogen protection, add 10 g of the intermediate, 10 g of 3-isocyanate-propyltrimethoxysilane, and 1 g of triethylamine to 100 ml of acetone, react at 75 °C for 1.5 h, and dry to obtain the product; 2) Under nitrogen protection, 10g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane and 6g of 3,3,3-trifluoropropylamine were added to 100ml of anhydrous ethanol, heated to 65℃ and reacted for 45h. After cooling to room temperature, 18g of the product obtained in step 1) and 30ml of 10wt% ammonia water were added, heated to 50℃ and reacted for 2.5h. After drying, fluorosilicone resin-1 was obtained.
[0035] Preparation Example 2 The preparation method of fluorosilicone resin-2 is the same as that of preparation example 1, except that the amount of 5,5,5-trifluoropentanol added in step (1) is 1.5 mol.
[0036] Preparation Example 3 The preparation method of fluorosilicone resin-3 is the same as that of preparation example 1, except that the amount of 3-isocyanate-propyltrimethoxysilane added in step (1) is 15g.
[0037] Preparation Example 4 The preparation method of fluorosilicone resin-4 is the same as that of preparation example 1, except that the amount of 3,3,3-trifluoropropylamine added in step (2) is 8g.
[0038] Preparation Example 5 The preparation method of fluorosilicone resin-5 is the same as that in preparation example 1, except that the amount of product added in step (2) is 21g.
[0039] Preparation Example 6 The preparation method of fluorosilicone resin-6 includes the following steps: Under nitrogen protection, 10g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane and 6g of 3,3,3-trifluoropropylamine were added to 100ml of anhydrous ethanol, heated to 65℃ and reacted for 45h. After cooling to room temperature, 18g of the product obtained in step 1) and 30ml of 10wt% ammonia water were added, heated to 50℃ and reacted for 2.5h. After drying, fluorosilicone resin-6 was obtained.
[0040] Example 1 An anti-corrosion electronic-grade coating agent, by weight, comprises the following raw materials: 6 parts acrylate, 15 parts tridefluorooctyl methacrylate, 10 parts fluorosilicone resin-1, 1.2 parts N-β-aminoethyl-γ-aminopropyltrimethoxysilane, 0.08 parts azobisisobutyronitrile, and 100 parts ethyl perfluorobutyl ether; wherein the acrylate is a mixture of methacrylate, hexanediol diacrylate, and pentaerythritol tetraacrylate, with a mass ratio of 1:0.4:0.2.
[0041] The preparation method of the anti-corrosion electronic-grade coating agent in this embodiment includes the following steps: Under nitrogen protection, acrylate, tridecyl fluorooctyl methacrylate, fluorosilicone resin-1, N-β-aminoethyl-γ-aminopropyltrimethoxysilane, azobisisobutyronitrile and ethyl perfluorobutyl ether were stirred at 65°C for 4.5 h and then rotary evaporated to obtain the coating agent.
[0042] Example 2 An anti-corrosion electronic-grade coating agent, by weight, comprises the following raw materials: 5 parts acrylate, 10 parts tridefluorooctyl methacrylate, 9 parts fluorosilicone resin-1, 0.6 parts N-β-aminoethyl-γ-aminopropyltrimethoxysilane, 0.06 parts azobisisobutyronitrile, and 80 parts ethyl perfluorobutyl ether; wherein the acrylate is a mixture of methacrylate, hexanediol diacrylate, and pentaerythritol tetraacrylate, with a mass ratio of 1:0.2:0.1.
[0043] The preparation method of the anti-corrosion electronic-grade coating agent in this embodiment includes the following steps: Under nitrogen protection, acrylate, tridecyl fluorooctyl methacrylate, fluorosilicone resin-1, N-β-aminoethyl-γ-aminopropyltrimethoxysilane, azobisisobutyronitrile and ethyl perfluorobutyl ether were stirred at 60°C for 12 h and then rotary evaporated to obtain the coating agent.
[0044] Example 3 An anti-corrosion electronic-grade coating agent, by weight, comprises the following raw materials: 8 parts acrylate, 20 parts tridecylfluorooctyl methacrylate, 11 parts fluorosilicone resin-1, 2 parts N-β-aminoethyl-γ-aminopropyltrimethoxysilane, 1 part azobisisobutyronitrile, and 130 parts ethyl perfluorobutyl ether; wherein the acrylate is a mixture of methacrylate, hexanediol diacrylate and pentaerythritol tetraacrylate, with a mass ratio of 1:0.5:0.3.
[0045] The preparation method of the anti-corrosion electronic-grade coating agent in this embodiment includes the following steps: Under nitrogen protection, acrylate, tridecyl fluorooctyl methacrylate, fluorosilicone resin-1, N-β-aminoethyl-γ-aminopropyltrimethoxysilane, azobisisobutyronitrile and ethyl perfluorobutyl ether were stirred at 70°C for 4 hours and then rotary evaporated to obtain the coating agent.
[0046] Example 4 An anti-corrosion electronic-grade coating agent and its preparation method are disclosed. The specific implementation method is the same as that in Example 1, except that fluorosilicone resin-1 is replaced with fluorosilicone resin-2 in an equal amount.
[0047] Example 5 An anti-corrosion electronic-grade coating agent and its preparation method are disclosed. The specific implementation method is the same as that in Example 1, except that fluorosilicone resin-1 is replaced with fluorosilicone resin-3 in an equal amount.
[0048] Example 6 An anti-corrosion electronic-grade coating agent and its preparation method are described. The specific implementation method is the same as that in Example 1, except that fluorosilicone resin-1 is replaced with fluorosilicone resin-4 in an equal amount.
[0049] Example 7 An anti-corrosion electronic-grade coating agent and its preparation method are disclosed. The specific implementation method is the same as that in Example 1, except that fluorosilicone resin-1 is replaced with fluorosilicone resin-5 in an equal amount.
[0050] Example 8 An anti-corrosion electronic-grade coating agent and its preparation method are described. The specific implementation method is the same as that in Example 1, except that fluorosilicone resin-1 is replaced with fluorosilicone resin-6 in an equal amount.
[0051] Example 9 An anti-corrosion electronic-grade coating agent and its preparation method are disclosed. The specific implementation method is the same as that in Example 1, except that fluorosilicone resin-1 is replaced with an equal amount of fluorosilicone resin LS-8722.
[0052] Performance testing The coating agents obtained in each embodiment and comparative example were diluted 30 times with Kefrier 400 solvent, coated onto a PCB substrate to a thickness of 50 μm, and then subjected to the following tests after curing and drying: Adhesion: Determined by the circular crossing method in GB / T 1720-1979(1989) "Determination of Adhesion of Paint Films"; Corrosion resistance: The static water contact angle of the coating surface was tested, referring to the national standard GB / T1771. The salt spray resistance test was conducted according to the "Determination of Neutral Salt Spray Resistance of Paints and Varnishes 2007". The time when each test sample started to bubble was observed. Five groups were tested for each group, and the average value was taken. Surface resistivity: Tested according to standard ASTM D257 at 25°C and 50%RH.
[0053] The test results are shown in Table 1: Table 1
[0054] As shown in Table 1, the anti-corrosion electronic-grade coatings of Examples 1-3 exhibit excellent adhesion, corrosion resistance, and insulation. A comparison of the data from Example 4 and Example 1 reveals that changing the ratio of maleic anhydride to 5,5,5-trifluoropentanol may reduce the residual carboxyl groups after ring-opening of maleic anhydride, affecting further reactions and leading to weakened corrosion resistance and insulation. A comparison of the data from Example 5 and Example 1 shows that changing the ratio of the intermediate to 3-isocyanate-propyltrimethoxysilane may cause the coating to become brittle and reduce adhesion. A comparison of Examples 6, 7, and Example 1 further demonstrates… The change in the ratio of γ-(2,3-epoxypropoxy)propyltrimethoxysilane to 3,3,3-trifluoropropylamine and the product can lead to uneven distribution of unreacted 3,3,3-trifluoropropylamine within the system, and may also affect the degree of crosslinking of the coating agent, resulting in a decrease in the adhesion or corrosion resistance of the coating. As can be seen from the comparison between Example 8 and Example 1, the adhesion and corrosion resistance of the coating obtained by polymerizing fluorosilicone resin with silane and fluorinated monomers are significantly reduced. As can be seen from the comparison between Example 9 and Example 1, the performance of the coatings decreased to varying degrees when using commercially available fluorosilicone resin.
[0055] The above embodiments are only for illustrating the technical concept and features of the present invention, and are intended to enable those skilled in the art to understand the content of the present invention and implement it. They should not be used to limit the scope of protection of the present invention. All equivalent changes or modifications made in accordance with the spirit and essence of the present invention should be covered within the scope of protection of the present invention.
Claims
1. A corrosion-resistant electronic-grade coating agent, characterized in that, By weight, it includes the following raw materials: 5-8 parts acrylate, 10-20 parts fluorinated acrylate, 9-11 parts fluorosilicone resin, 0.6-2 parts coupling agent, 0.06-1 part initiator, and 80-130 parts hydrofluoroether.
2. The anti-corrosion electronic-grade coating agent according to claim 1, characterized in that, The acrylate is a mixture of acrylic acid, methacrylic acid and its derivatives, hexanediol diacrylate, ethylene glycol dimethacrylate, ethoxylated trimethylolpropane triacrylate, trimethylolpropane triacrylate, pentaerythritol triacrylate and pentaerythritol tetraacrylate.
3. The anti-corrosion electronic-grade coating agent according to claim 1, characterized in that, The fluorinated acrylate is any one or more of tridecylfluorooctyl methacrylate, dodecafluoroheptyl methacrylate, and hexafluorobutyl methacrylate.
4. The anti-corrosion electronic-grade coating agent according to claim 1, characterized in that, The preparation method of the fluorosilicone resin includes the following steps: 1) Maleic anhydride, 5,5,5-trifluoropentanol, and a polymerization inhibitor are added to toluene and reacted at 45-55℃ for 24-36 h. After drying, an intermediate is obtained. Under nitrogen protection, the intermediate, 3-isocyanate-propyltrimethoxysilane, and triethylamine are added to acetone and reacted at 70-80℃ for 1-2 h. After drying, the product is obtained. 2) Under inert gas protection, γ-(2,3-epoxypropoxy)propyltrimethoxysilane and 3,3,3-trifluoropropylamine were added to anhydrous ethanol, heated to 60-70℃ and reacted for 40-50 h, cooled to room temperature, and then the product obtained in step 1) and ammonia water were added, heated to 45-55℃ and reacted for 2-3 h, and dried to obtain fluorosilicone resin.
5. The anti-corrosion electronic-grade coating agent according to claim 4, characterized in that, In step 1), the molar ratio of maleic anhydride to 5,5,5-trifluoropentanol is 1:(1-1.2).
6. The anti-corrosion electronic-grade coating agent according to claim 4, characterized in that, The mass ratio of the intermediate described in step 1) to 3-isocyanate-propyltrimethoxysilane is 1:(0.8-1.3).
7. The anti-corrosion electronic-grade coating agent according to claim 4, characterized in that, In step 2), the mass ratio of γ-(2,3-epoxypropoxy)propyltrimethoxysilane to 3,3,3-trifluoropropylamine and the product is 1:(0.5-0.7):(1.5-2).
8. The anti-corrosion electronic-grade coating agent according to claim 1, characterized in that, The coupling agent is any one or more of γ-(methacryloyloxy)propyltrimethoxysilane, 3-aminopropyltriethoxysilane, and N-β-aminoethyl-γ-aminopropyltrimethoxysilane.
9. The anti-corrosion electronic-grade coating agent according to claim 1, characterized in that, The hydrofluoroether is any one or more of the following: methyl nonafluorobutyl ether, methyl nonafluoroisobutyl ether, methyl perfluoropropyl ether, ethyl perfluorobutyl ether, 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl ether, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, trifluoroethyl hexafluoropropyl ether, perfluorononylpentafluoroethyl ether, and 3-methoxyperfluoroethane.
10. A method for preparing an anti-corrosion electronic-grade coating agent according to any one of claims 1-9, characterized in that, Includes the following steps: Under nitrogen protection, acrylate, fluorinated acrylate, fluorosilicone resin, coupling agent, initiator and hydrofluoroether are stirred at 60-70℃ for 4-12 hours and then rotary evaporated to obtain coating agent.
Citation Information
Patent Citations
Highly transparent washable acrylic anti-corrosion coating and its preparation method
CN113683934B